Cell free DNA as a marker of training status in weightlifters - Jeremy A. Gentles; William G. Hornsby; Christine L. Coniglio; Andrew R. Dotterweich; Jon A. Miller; Charles A. Stuart; Michael H. Stone (Termedia Publishing House, 2017)
The purpose of this investigation was to elucidate the changes in cf-DNA as it relates to fluctuations in resistance training workloads and intensities. The relationship between cell free DNA (cf-DNA), C-reactive protein (CRP), creatine kinase (CK), testosterone (T), cortisol (C), testosterone-cortisol ratio (T:C), body mass and body composition were also examined. Eight weightlifters (5 males and 3 females, age = 25 ± 3.5 yr, body mass = 88.3 ± 22.7 kg, height = 173.8 ±8.4 cm) volunteered to participate in this study. Venous blood samples, body mass and body composition were taken six times, each corresponding to the end of a training phase. CK (p = 0.018, η² = 0.409) and CK %Δ (p < 0.001, η² = 0.594) were the only biochemical variables to reach statistical significance at any point. A number of statistically significant correlations were found among variables. VLD4wk was related to CK %Δ (r = 0.86), VLD4wk %Δ was related CK %Δ (r = 0.86) and TID1wk was related to CRP (r = 0.83). cf-DNA %Δ was correlated with CRP and CRP %Δ (r = 0.83 and 0.86, respectively). CRP and CRP %Δ were correlated with BF % (r = 0.94 and 0.92, respectively). CK and CK %Δ were both related to T:C (r = 0.94 and 0.89, respectively) and T:C %Δ (r = 0.87 and 0.86, respectively). The correlation between cf-DNA and CRP suggests that cf-DNA may be a valuable indicator of inflammation in weightlifters.